The role of XMM‐Newton for present and next‐generation Sunyaev–Zeldovich experiments. Issue 2 (22nd March 2017) - Pointecouteau, E.
Abstract : A strong synergy exists between observations of the hot gas trapped in the potential well of galaxy clusters at X‐ray wavelengths and through the Sunyaev–Zeldovich (SZ) effect. XMM‐Newton has been a major asset in joint scientific analysis with data from the current generation of SZ instruments such as Planck, SPT, or ACT. I review the main X‐ray and SZ results from the past years. I discuss the expectations and perspectives for upcoming and future measurements of the SZ signal and their combination with X‐ray data, focusing on the role to be played by XMM‐Newton in these studies.